Presidential Decree as the Norm in Legal Politics (A Comparative of the Presidential Decree in Tunisia and Indonesia During Soekarno and Abdurrahman Wahid) - Ahmad, Jafar; Fadillah, Nisaul (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2021)
This article investigates a legal politics in Tunisia and Indonesia focuses the fate of the presidential decree in Tunisia in the dissolution of Parliament context. Did it succeed or fail? This analysis is obtained through a comparative study of the same pattern in Indonesia, namely the presidential decree during the Soekarno leadership and Abdurrahman Wahid or Gus Dur. The data is obtained through literature studies such as scientific books and journals. Researchers also construct the data through online media studies both at domestic and abroad. The results of this study illustrate how the pattern of the Presidential decree in Tunisia on July 27th, 2021. It has similarities with the presidential decree that occurred during the Soekarno Presidential era on July 5th, 1959. Military forces fully supported the decree that led to the dissolution of Parliament. Unlike Gus Dur, who stepped down from his post after issuing a decree. Kais Saied's decree in Tunisia is predicted to be a success and perpetuate his reign as President.